MODEL KAMPUS RESPONSIF GENDER DALAM MEWUJUDKAN PENDIDIKAN TINGGI YANG INKLUSIF DAN BERKEADILAN - Sakina; Nenny Kurniati; M. Iksan Kahar (Musawa: Journal for Gender Studies, 2026)
This study aims to develop a gender-responsive campus model for promoting inclusive and equitable higher education through an institutional governance perspective. Employing a qualitative approach with a library research design, the study analyzes theories, empirical studies, policy documents, and international publications on gender mainstreaming, university governance, and inclusive education. Data were examined using content and thematic analysis to formulate a conceptual framework for gender-responsive higher education governance. The findings indicate that a gender-responsive campus should be implemented as an integrated governance system consisting of nine key components: gender-responsive leadership, institutional policies and regulations, gender-responsive curriculum, human resource management, inclusive academic services, gender-friendly facilities and infrastructure, prevention and response mechanisms for sexual violence, active participation of the academic community, and continuous monitoring and evaluation. The effectiveness of the model depends on institutional commitment, comprehensive regulations, adequate resources, and collaborative stakeholder engagement, while limited gender awareness, organizational resistance, and weak institutional coordination remain major challenges. This study contributes a conceptual governance model that can guide higher education institutions in strengthening gender equality, inclusiveness, and social justice while supporting the achievement of Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 5 (Gender Equality).